Two decades of dynamic change and progressive destabilization on the Thwaites Eastern Ice Shelf - Alley, Karen E.; Wild, Christian T.; Luckman, Adrian; Scambos, Ted A.; Truffer, Martin; Pettit, Erin C.; Muto, Atsuhiro; Wallin, Bruce; Klinger, Marin; Sutterley, Tyler; Child, Sarah F.; Hulen, Cyrus; et al. (The cryosphere, 2021)
The Thwaites Eastern Ice Shelf (TEIS) buttresses the eastern grounded portion of Thwaites Glacier through contact with a pinning point at its seaward limit. Loss of this ice shelf will promote further acceleration of Thwaites Glacier. Understanding the dynamic controls and structural integrity of the TEIS is therefore important to estimating Thwaites' future sea-level contribution. We present a ∼ 20-year record of change on the TEIS that reveals the dynamic controls governing the ice shelf's past behaviour and ongoing evolution. We derived ice velocities from MODIS and Sentinel-1 image data using feature tracking and speckle tracking, respectively, and we combined these records with ITS_LIVE and GOLIVE velocity products from Landsat-7 and Landsat-8. In addition, we estimated surface lowering and basal melt rates using the Reference Elevation Model of Antarctica (REMA) DEM in comparison to ICESat and ICESat-2 altimetry. Early in the record, TEIS flow dynamics were strongly controlled by the neighbouring Thwaites Western Ice Tongue (TWIT). Flow patterns on the TEIS changed following the disintegration of the TWIT around 2008, with a new divergence in ice flow developing around the pinning point at its seaward limit. Simultaneously, the TEIS developed new rifting that extends from the shear zone upstream of the ice rise and increased strain concentration within this shear zone. As these horizontal changes occurred, sustained thinning driven by basal melt reduced ice thickness, particularly near the grounding line and in the shear zone area upstream of the pinning point. This evidence of weakening at a rapid pace suggests that the TEIS is likely to fully destabilize in the next few decades, leading to further acceleration of Thwaites Glacier.